ANALISIS YURIDIS PENYELESAIAN PERSELISIHAN KONTRAK AKIBAT KETERLAMBATAN PEMBAYARAN ( STUDI TERHADAP PERJANJIAN KERJASAMA JUAL BELI TANDAN BUAH SEGAR PTPN II DENGAN REKANAN/ PEMASOK) - YUDHISTIRA CRIESA ZEFANI TARIGAN CRIESA ZEFANI TARIGAN (PREMISE LAW JURNAL, 2015)
The business world, an agreement in a transaction is very important to be realized by embodying it into a contract. This is done in order to avoid any problems which arise at the time the agreement is being implemented. Therefore,the writing of a contract is intended to provide legal certainty and the clarity of the right and obligation of both parties. In this research, the researcher would analyze the settlement of dispute in a contract because of the overdue payment in a contract between PT Perkebunan Nusantara II and CV Bina Mandiri on the Trade of TBS (fresh oil palm hands) at PKS Kwala Saw it, PTPN II (Persero). The problems in the research were as follows: how about the right and obligation of the parties in the mutual agreement on the trade of oil palm fresh hands at PKS Kwala Sawit PTPN II, Tanjung Morawa, how about the protection on TBS supplier when PTPN II did overdue payment because they did not have cash was that PTPN II was considered as breaching the contract (default); therefore, CV Bina Mandiri could file a complaint for PKS Kwala Sawit PTPN II Tanjung Morawa, because the latter was default. The settlement of the overdue payment by PTPN II to the supplier who sustained loss, based on their mutual agreement could be done by reconciliation. When reconciliation could not settle the dispute it was settled by litigation before the District Court at Stabat, where the contract was made.   Keywords: Dispute, Contract, Overdue Payment